2015
DOI: 10.18043/ncm.76.4.205
|View full text |Cite
|
Sign up to set email alerts
|

Practice Characteristics and Geographic Distribution of Clinical Pharmacist Practitioners in North Carolina

Abstract: Active CPPs most often come from ambulatory care backgrounds. Few CPPs are practicing in rural areas, a circumstance that may be related to financial viability, as most CPP practice in, and are compensated by, larger institutions such as academic health centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The lack of work experience worsened the situation mentioned above [ 33 ]. The majority of respondents hold a primary or medium professional title and are aged around 31, with average working seniority of around five years.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of work experience worsened the situation mentioned above [ 33 ]. The majority of respondents hold a primary or medium professional title and are aged around 31, with average working seniority of around five years.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of CPPs published in 2015 indicated that there were 87 active CPPs across North Carolina [7]. The majority (76%) practiced in ambulatory care clinics, including hospital-based clinics and physician group practices [7].…”
Section: Clinical Pharmacist Practitionersmentioning
confidence: 99%
“…The majority (76%) practiced in ambulatory care clinics, including hospital-based clinics and physician group practices [7]. Only 7% of CPPs practiced in rural communities, and 43 rural counties did not have a CPP.…”
Section: Clinical Pharmacist Practitionersmentioning
confidence: 99%
See 2 more Smart Citations